2014
DOI: 10.1021/ja500275r
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Stepwise Electroless Deposition Enables a Remarkably Facile Synthesis of Highly Active and Stable Amorphous Pd Nanoparticle Electrocatalysts for Oxygen Reduction Reaction

Abstract: This paper reports on highly active and stable amorphous Pd nanoparticle electrocatalysts for the oxygen reduction reaction. The amorphous catalysts were synthesized by a remarkably facile and quick electroless deposition process newly developed in this study (process time <5 min). An electrode substrate (glassy carbon, carbon cloth) was sequentially dipped for 10 s into two separate solutions of a reducing agent (sodium hypophosphite (NaH2PO2)) and Pd ions to deposit amorphous Pd nanoparticles containing phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 45 publications
4
126
0
Order By: Relevance
“…913 A typical example is the use of Ni 2 P as a cocatalyst for Pd/C to form a Pd–Ni 2 P/C nano-electrocatalyst which not only shows remarkable catalytic activity, but also exhibits impressive corrosion resistance in acidic medium. 9 In addition, Tang et al demonstrated that alloying Pd with P can lead to a decrease in the adsorption strength and adsorption amount of CO. 10 In this regard, alloying Pt with the nonmetallic element phosphorus seems to hold great promise to address the stability limitations of Pt-based catalysts for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…913 A typical example is the use of Ni 2 P as a cocatalyst for Pd/C to form a Pd–Ni 2 P/C nano-electrocatalyst which not only shows remarkable catalytic activity, but also exhibits impressive corrosion resistance in acidic medium. 9 In addition, Tang et al demonstrated that alloying Pd with P can lead to a decrease in the adsorption strength and adsorption amount of CO. 10 In this regard, alloying Pt with the nonmetallic element phosphorus seems to hold great promise to address the stability limitations of Pt-based catalysts for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Such disordered structure suffers from low stability in the corrosive electrochemical environment and only moderate activity improvement. [22,23] From the structural perspective,t he ordered intermetallic phases,w ith definite composition and structure,c an provide the predictable control over structural, geometric, and electronic effects for catalysis optimization, which cannot be afforded by the widely created conventional alloys. [24][25][26] Especially,t he ordered intermetallic nanocrystals usually exist the strong electron interaction and the change of the bond length and electron configuration, which could significantly improve their catalytic activities for both ORR and oxidation reactions of fuels.…”
mentioning
confidence: 99%
“…The improved durability might be attributed to the strong interaction between the 2D C 3 N 4 nanosheets and Pd nanoparticles, which made Pd less vulnerable to dissolution, and aggregation compared to Pd nanoparticles. [37,38] To further understand the intrinsic activity of the C 3 N 4 /Pd composites, we estimated the ECSA of C 3 N 4 /Pd composites and commercial Pt/C by integrating the amount of charges in the corresponding CV curves [39,40] ( Figure S3). The results showed that C 3 N 4 /Pd composites and commercial Pt/C had an ECSA of 58 m 2 /g Pd , 56 m 2 /g Pt ( Figure 5A), respectively.…”
Section: 1mentioning
confidence: 99%